How does water stress affect Corymbia citriodora (Hook.) K.D. Hill & L.A.S. Johnson throughout the initial growth phase? - De Medeiros, Robson Luis Silva [UNESP]; De Souza, João Vitor Oliveira [UNESP]; Fernandes, João Pedro Peixoto [UNESP]; De Oliveira, Reginaldo [UNESP]; Gratão, Priscila Lupino [UNESP]; De Paula, Rinaldo Cesar [UNESP] (My University, 2023)
Corymbia citriodora has the potential to be used in the expansion of the forestry sector in Brazil, as it presents greater tolerance to abiotic stresses than other commonly cultivated species. The plants are exposed to several stress events throughout their cycle that can compromise their growth and development. This study aimed to evaluate physiological, biochemical, and growth characteristics in C. citriodora plants grown under different irrigation regimes at different ages. Plants of C. citriodora grown in pots were submitted to five irrigation regimes (20, 35, 50, 65, and 80% of the maximum soil water retention capacity) for 105 days in a greenhouse. Plant growth, gas exchange, leaf water potential, chlorophyll, carotenoids, and proline contents, and lipid peroxidation by MDA content were evaluated at the end of this period. More restrictive irrigation regimes reduced seedling growth. Water availability affected physiological, biochemical, and morphological parameters. Water stress associated with plant growth increased stress levels.
Keywords: eucalyptus; forest seedlings; Gas exchange; morphological adaptations